Efficacy of repetitive transcranial magnetic stimulation for consciousness recovery in children with disorders of consciousness following traumatic brain injury - Zheng, Nan; Zou, Zhuo; Wang, Wenjuan; Dong, Fangling; He, Xuemei; Ren, Jian; Liu, Xiaoyan; Zhang, Yangping; Su, Zhongjian (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the efficacy of 5 Hz repetitive transcranial magnetic stimulation (rTMS) over the left dorsolateral prefrontal cortex (left DLPFC) for consciousness recovery in children with disorders of consciousness (DOC) following traumatic brain injury (TBI).MethodsThis randomized controlled trial included 98 pediatric patients aged ≥2 years with DOC after TBI, admitted to Kunming Children’s Hospital from January 2023 to July 2025. Patients were randomly divided into an experimental group (n = 49) and a control group (n = 49). The experimental group received 5 Hz rTMS targeting the left DLPFC (80% resting motor threshold, 1,000 pulses per session, totaling 20 min), combined with conventional rehabilitation therapy (once daily for 3 weeks). The control group received only conventional rehabilitation therapy. The primary efficacy outcomes included serum neuron-specific enolase (NSE) level, Coma Recovery Scale-Revised (CRS-R) score, Glasgow Coma Scale (GCS) score, and level of consciousness before and after treatment.ResultsAfter 3 weeks of intervention, the experimental group demonstrated statistically significant improvements compared to both baseline status and the control group (p < 0.05). The experimental group demonstrated a significant reduction in serum NSE levels, a significant increase in CRS-R and GCS scores, and a significant improvement in the level of consciousness. No adverse events (including seizures) were observed throughout the treatment.ConclusionThis study provided the first clinical evidence that the combined application of 5 Hz rTMS targeting the left DLPFC is a safe and effective intervention for promoting the recovery of consciousness in children with DOC following TBI. Significant improvements in behavioral scales (CRS-R, GCS) and reduced levels of the neurological injury marker (serum NSE) suggest that this protocol exerts dual effects of promoting arousal and neuroprotection. This novel treatment approach, designed based on the characteristics of pediatric neurological development, offers a promising non-invasive neuromodulation strategy for this challenging patient population, filling a critical evidence gap in this field.